2006
DOI: 10.1167/iovs.05-1392
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film, Contact Lens, and Patient-Related Factors Associated with Contact Lens–Related Dry Eye

Abstract: Contact lens-related dry eye may be explained mechanistically by increased tear film thinning times (evaporation or dewetting) resulting in increased tear film osmolality. Other contributing factors include the use of high-water-content lenses, which have traditionally been reported to be associated with less patient comfort than lower-water-content lenses, potentially due to spoilation and deposition. As found in other studies of dry eye, women are more likely to report contact lens-related dry eye than are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
256
6
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(282 citation statements)
references
References 69 publications
(52 reference statements)
9
256
6
11
Order By: Relevance
“…115 However, other authors reported no association between MGDo in the lower eyelid and CL wear. 117 The disagreement in study results is possibly because of the authors from the latter study not examining or imaging the full extent of both upper and lower eyelids, but rather only the central portion of the lower eyelid.…”
Section: Meibomian Gland Dropoutmentioning
confidence: 90%
“…115 However, other authors reported no association between MGDo in the lower eyelid and CL wear. 117 The disagreement in study results is possibly because of the authors from the latter study not examining or imaging the full extent of both upper and lower eyelids, but rather only the central portion of the lower eyelid.…”
Section: Meibomian Gland Dropoutmentioning
confidence: 90%
“…However, if dry eye tests were used, no consensus has been reached regarding the optimal appropriate diagnostic criterion are or combination of criteria. 24,25 We did not assess certain factors such as wearing of contact lens, [26][27][28] LASIK surgery, 29 keratoplasty 12 eyelid and conjunctival disease, 30 allergic conjunctivitis, 31 seventh nerve palsy, 32 gout, 33 total body irradiation, 34 Sjogren's syndrome, 35 and participants' compliance with dry eye treatment, 36 which might be associated with symptomatic dry eye and diminished visual function.…”
Section: Eyementioning
confidence: 99%
“…6 Recent studies have demonstrated that questioning of SCL wearers about symptoms has more diagnostic value than clinical testing. 7 McMonnies developed a dry eye questionnaire8 and found a high level of sensitivity in detecting both dry eye and marginal dry eye.…”
Section: Tear Film Evaluation In Contact Lensmentioning
confidence: 99%